An Energy-Efficient Signal Detection Scheme for a Radar-Communication System Based on the Generalized Approximate Message-Passing Algorithm and Low-Precision Quantization - Xia, De-Ping; Zhang, Yu; Cai, Peixiang; Huang, Ling (IEEE access, 2019)
Integrated radar-communication systems will play an important role in the future battlefield scenarios by decreasing the interference, volume, weight, and power consumption of equipment and promoting information fusion with an enhanced network. An active electronically scanned array radar system is ideal for such scenarios. However, a few studies have focused on the modeling and detection of communication signals for such integrated systems. In this paper, an array division strategy is developed, and a low-complexity signal detection scheme based on the generalized approximate message-passing (GAMP) algorithm is implemented. Furthermore, a quantization model is introduced into the output function of the GAMP algorithm. The method effectively provides communication signal detection with low-precision quantization and outperforms the linear minimum mean square error-based algorithm at the same precision levels. Overall, an energy-efficient radar-communication strategy is developed to promote the application of such systems in the future battlefield scenarios.